Non-Hodgkin's lymphoma associated with primary Sjögren's syndrome. (1992)
OBJECTIVES: To evaluate the prevalence, the incidence and clinical presentation of non-Hodgkin's lymphoma associated with primary Sjögren's syndrome. METHODS: Sixty-two patients with primary Sjögren's syndrome were analyzed retrospectively in an open investigation. RESULTS: Of 62 patients with primary Sjögren's syndrome, 4 of them (6.4%) developed non-Hodgkin's lymphoma (6.9 cases per 1000 per year). All of them were women. Non-Hodgkin's lymphoma always developed after the onset of primary Sjögren's syndrome with a time interval ranging from 3 to 27 years. Pathological findings showed two diffused mixed small and large cell cleaved lymphomas and two diffused large cell cleaved lymphomas. Three cases had extra-nodular localizations. All of these 4 patients are still alive and in complete remission 2 to 8 years after the diagnosis of non-Hodgkin's lymphoma. CONCLUSION: This study confirms the association of non-Hodgkin's lymphoma in primary Sjögren's syndrome. These non-Hodgkin's lymphomas frequently had extra-nodal localizations. Good sensitivity to treatment, when necessary, provided good prognosis.